Genipin Cross-Linked Chitosan-Polyvinylpyrrolidone Hydrogels: Influence of Composition and Postsynthesis Treatment on pH Responsive Behaviour - Chinyelumndu Jennifer Nwosu; Glenn Adam Hurst; Katarina Novakovic (Advances in Materials Science and Engineering)
Understanding the factors that influence the pH responsive behaviour of biocompatible cross-linked hydrogel networks is essential when aiming to synthesise a mechanically stable and yet stimuli responsive material suitable for various applications including drug delivery and tissue engineering. In this study the behaviour of intelligent chitosan-polyvinylpyrrolidone-genipin cross-linked hydrogels is examined as a function of their composition and postsynthesis treatment. Hydrogels are synthesised with varying amounts of each component (chitosan, polyvinylpyrrolidone, and genipin) and their response in a pH 2 buffer is measured optically. The influence of postsynthesis treatment on stability and smart characteristics is assessed using selected hydrogel samples synthesised at 30, 40, and 50°C. After synthesis, samples are exposed to either continuous freezing or three freeze-thaw cycles resulting in increased mechanical stability for all samples. Further morphological and mechanical characterisations have aided the understanding of how postsynthesis continual freezing or freeze-thaw manipulation affects network attributes.